1998
DOI: 10.1088/0952-4746/18/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of C3H 10T1/2 cells by low doses of ionising radiation: a collaborative study by six European laboratories strongly supporting a linear dose-response relationship

Abstract: For the assessment of radiation risk at low doses, it is presumed that the shape of the low-dose-response curve in humans for cancer induction is linear. Epidemiological data alone are unlikely to ever have the statistical power needed to confirm this assumption. Another approach is to use oncogenic transformation in vitro as a surrogate for carcinogenesis in vivo. In mid-1990, six European laboratories initiated such an approach using C3H 10T1/2 mouse cells. Rigid standardisation procedures were established f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…It is emphasized that the findings of Mill et al . (56) are not in contradiction to the data of Redpath et al . (15), Azzam et al .…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…It is emphasized that the findings of Mill et al . (56) are not in contradiction to the data of Redpath et al . (15), Azzam et al .…”
Section: Discussionsupporting
confidence: 56%
“…In the current study, a biologically based multistage model for chromosome aberrations and in vitro neoplastic transformation has been tested on various data sets from cell culture studies. While the limitations of cell culture studies have been stated (56), one advantage is that they allow investigations of biological mechanisms that are relevant for human exposure at low doses. The current work focuses on two important low-dose effects that have been discovered in recent years: detrimental bystander effects (25) and protective apoptosis-mediated bystander effects (7, 20–23, 50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has to do with the different dose rates applied, different experimental protocols including delayed plating and the fact H. Schöllnberger and P. M. Eckl that many of these other studies have a lowest dose that is too high to reveal any possible protective effects. For example, the lowest dose in the X-ray data by Mill et al (1998) is at 250 mGy while Redpath et al (2003) and Ko et al (2004) found the transition between protection and detriment from X-ray exposures at lower doses. This has been discussed in more detail by Schöllnberger et al (2002) and Schöllnberger et al (submitted).…”
Section: Discussionmentioning
confidence: 99%
“…13 Perhaps, the most plausible in vitro model for radiation-induced cancer is in vitro oncogenic transformation, but, even for this, end point studies at doses ≤1 mGy are not feasible. 14,15 …”
Section: What Is Known At Lower Radiological Dosesmentioning
confidence: 99%